2014
DOI: 10.2152/jmi.61.446
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Tight Hamstrings Following Conservative Treatment for Apophyseal Ring Fracture in Adolescent Athletes: Critical Appraisal

Abstract: : Apophyseal ring fracture is a unique disease in children and adolescents. Its clinical features include low back pain, sciatica, paravertebral muscle spasm and tenderness, restricted back motion, neurological symptoms, and tight hamstrings. For all athletes, body flexibility is one of the most important factors for better performance. Therefore, persistent tight hamstrings has a negative influence on athletic performance. In this report, we present two adolescent athletes with apophyseal ring fracture treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Half of the patients had to undergo surgical decompression because of epiphyseal ring rupture and compression symptoms. Surgical treatment is the most effective and main treatment for PRAF21. Currently, the choice of surgical method for lumbar PRAF is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the patients had to undergo surgical decompression because of epiphyseal ring rupture and compression symptoms. Surgical treatment is the most effective and main treatment for PRAF21. Currently, the choice of surgical method for lumbar PRAF is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…2. Chronic compression of the nerve root by both the bony fragment and the HNP would have caused the tight hamstrings (6), which in turn would not be good for professional performance. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, patients are treated with conservative management (1) ; however, the clinical features tend to be prolonged and the patient could eventually require surgical intervention to remove the bony fragment (2). Even though conservative treatment would be effective to reduce pain, the residual bony fragment may cause spinal canal stenosis (1) or tightness of the hamstrings (6).…”
Section: Introductionmentioning
confidence: 99%
“…(4,5) The prevalence of hamstring tightness in athletes has been a subject of numerous studies in the past decade.and main cause of concern because it lead to loss of function ,reduce performance and longer recovery time. (6) A study by Gabbe et al (2010) found that hamstring tightness is prevalent in 40% of athletes, particularly those involved in sports requiring high-speed running and sudden stops. (7) Similarly, a study by Witvrouw et al reported a 37% prevalence rate among professional soccer players.…”
Section: Introductionmentioning
confidence: 99%